IMPROVING STUDENTS’ SPEAKING PROFICIENCY BY USING SPEAKING BOARD GAMES FOR ELEMENTARY STUDENTS AT EDUPRANA LANGUAGE COURSE PALANGKARAYA KALIMANTAN TENGAH - Norhayati, Norhayati (P3M Politeknik Negeri Tanah Laut, 2016)
There are so many techniques which can be implemented by teachers inorder to support teaching learning process. Some techniques are also usefulfor improving students’ speaking proficiency. In Eduprana LanguageCourse, which offer Speak Out program for the young learners, the methodsin practicing speaking mostly used role-play method. In this method,students are required to practice conversation based on the situations thatare provided in module learnt. This method, somehow, make the practice ofspeaking be boring and monotone. In order to solve this problem, theteachers are required to be more creative so the class atmosphere be moreinteresting and students be more creative in speaking. The usage of game inteaching learning process has been known can give positive impact forlearning experiences. So, in this study, the writer tried to implement theusage of speaking board games in order as an effort of improving students’speaking proficiency. The method of this study is class actions research,where in this study there are two cycles that are being conducted. The resultof the study showed significant increasing point of pre-test and post-test offour variables in this study; vocabulary 2.51 to 3.11, pronunciation 2.41 to3.16, grammar 2.65 to 3.00, fluency 2.66 to 3.13. So, it can be concludedthat; 1) it is important to provide activities which engage the students’participation in the speaking activities and give them more chance to speak,such as playing board games which attracts the students’ attention andmake them enthusiastic to join the lesson. 2) Playing board games engagedthe students to speak up. When the students were playing the games, allof them had the same proportion to speak.Keywords: Speaking proficiency, board game, language course